The Use of Movies in Increasing Students' Critical Thinking Ability - Aannova Haryani; Muhammad Riko Yohansyah; Arifmiboy (CV. ITTC INDONESIA, 2024)
In this study, the authors used movies to improve students' critical thinking. This study used a quasi-experiment and purposive sampling. The population is all students of class VIII at MTsN 7 Agam. Class VIII.1 was taken as a sample. Understanding and critical thinking of students who think in forms are used as instruments for this research. Research data were analyzed quantitatively. The results of the study include: 1) using movies is better than students studying conventionally. 2) students' critical thinking is better by using movies than by using conventional learning. After being examined, it turns out that movies improve students' critical thinking skills rather than using conventional learning. The movie used can be adapted to the situation and conditions of the teaching and learning process.